Making public pasts : the contested terrain of Montréal's public memories, 1891-1930 - Gordon, Alan, 1968- (Studies on the history of Quebec., 2001)
Between 1891 and 1930 Montreal was a bilingual and increasingly multicultural city. Its "two majorities" struggled to negotiate and commemorate their respective memories in the public spaces of the city, using historic monuments to stake a claim to specific places, streets, and neighbourhoods. In Making Public Pasts Alan Gordon argues that the contest was fundamentally ideological, a competition between major social groups to shape perceptions of history and frame the historical consciousness of individuals.